Genomic analyses of polysaccharide capsules in Neisseria species - Clemence, M (2019)
Neisseria meningitidis is one of several Neisseria species that asymptomatically colonise the human nasopharynx. Occasionally, N. meningitidis invades the bloodstream, resulting in invasive meningococcal disease (IMD). In most settings, expression of a serogroup A, B, C, W, X or Y polysaccharide capsule is essential for IMD. Previously, capsules were considered unique to N. meningitidis, among the Neisseria, possibly acquired by horizontal genetic transfer (HGT). In this thesis, genomic analyses further investigate the distribution and evolution of capsules in Neisseria species.